Extension and Testing of Motorcycle Speedometer Accuracy Using Portable Speedometer Tester Testing Equipment Based on Arduino to Improve Driving Safety in Bali at Sma Negeri 1 Tabanan - Arif Devi Dwipayana; Aris Budi Sulistyo; Beny Dwifa; Surya Aji Ermanto; I Gusti Bagus Eka Nitiyasa; Dinda One Mulyaningtyas (Jurnal Pengabdian Kepada Masyarakat Semangat Nyata Untuk Mengabdi (JKPM Senyum), 2022)
The average age range for motorcycle users is the age range of 17 to 25 years, where this age is included in the productive age. The negative impact caused by this is an increase in the number of traffic accidents, according to data from the Directorate General of Land Transportation of the Ministry of Transportation, in 2020 when viewed from the profile of traffic accident victims based on education level, the biggest victims are students with a high school education level as much as 80,641 people. The background of the importance of the speedometer in vehicles is the safety factor, because a good driver always pays attention to the comparison of the speed of the vehicle he is driving with the condition of the road or terrain traversed. With a good and correct speedometer, the driver can calculate the speed that is adjusted to the existing situation and conditions. The purpose of this PKM activity is to provide information and understanding of the importance of the speedometer function on a motorcycle as a means of controlling speed while driving which later is expected to make students able to drive safely and safely while at the same time reducing the rate of traffic accidents, especially the productive age range (17 to 25). year). The method used is to conduct socialization and practice in the field. During the PKM activity until the end, the students were very enthusiastic about participating in the entire series of activities and hoped that these activities could be carried out regularly every year. Hopefully what has been given can have a positive and useful impact.